2020
DOI: 10.32674/jis.v11i2.2038
|View full text |Cite
|
Sign up to set email alerts
|

The differential impact of learning experiences on international student satisfaction and institutional recommendation

Abstract: This research uses data from i-graduate’s International Student Barometer to investigate the impact of student learning experiences on institutional satisfaction and recommendation for degree-seeking international students. Analyses revealed that evaluations – i.e., how satisfied students are with their experience – are influenced by different learning experience variables from those that impact behavioral intentions – i.e., their willingness to recommend the institution. This study finds that, within the lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Both international and domestic students were broadly satisfied with their study experience in Ireland, a trend identified elsewhere (Ammigan et al, 2020). Originating from a national cultural context with high power distance-that is, the extent to which individuals accept unequal distribution of power-marginally increased the academic satisfaction of students, regardless of the level of individualism.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Both international and domestic students were broadly satisfied with their study experience in Ireland, a trend identified elsewhere (Ammigan et al, 2020). Originating from a national cultural context with high power distance-that is, the extent to which individuals accept unequal distribution of power-marginally increased the academic satisfaction of students, regardless of the level of individualism.…”
Section: Discussionmentioning
confidence: 69%
“…Recognizing the role of culture in the experiences of international students (Neto, 2019), this article tests whether cultural distance is associated with academic satisfaction. This allows for better targeting of institutional support (Ammigan et al, 2020) as well as leveraging the experiences of international students to also enhance support for domestic students (Mihut, 2019). Culture can also manifest in the marketization of the education system (Tomlinson, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the context of the hospitality sector, it is widely accepted that service quality and price influence customer satisfaction and determine customer recommendations (Belanche et al, 2021). Ammigan et al (2021) confirm this relationship in the context of international institute recommendations.…”
Section: Introductionmentioning
confidence: 90%
“…Yet other studies have highlighted successful integration of international students, particularly from Eastern European contexts (Jankowska, 2011). Previous studies have also highlighted that the nationality and destination country of international students matter both for overall satisfaction and the willingness to recommend their experience to other students (Ammigan et al, 2021). Several studies on the experiences of international students at Irish universities have been conducted.…”
Section: Background and Previous Studiesmentioning
confidence: 99%